Transnational Russian studies - Byford, Andy, 1972-; Doak, Connor; Hutchings, Stephen C. (Transnational modern languages., 2020)
This book focuses on how Russia has perpetually redefined Russianness in reaction to the wider world. Treating culture as an expanding field, it offers original case studies in Russia's imperial entanglements; the life of things 'Russian', including the language, beyond the nation's boundaries, and Russia's positioning in the globalized world.